Straus: as duas sociologias médicas Straus: the two medical sociologies - Everardo Duarte Nunes (Universidade de São Paulo, 2007)
Analisou-se o trabalho pioneiro de Robert Straus, de 1957, denominado "The nature and status of Medical Sociology". Straus, um dos fundadores da sociologia médica, trouxe contribuições fundamentais para o campo e criou o primeiro departamento de ciências do comportamento em uma escola médica. No texto analisado, Straus estabelece as diferenças entre sociologia na medicina e sociologia da medicina. São apresentados comentários sobre a perspectiva atual da sociologia médica e sobre o autor. Robert Straus' pioneer work, "The nature and status of Medical Sociology," written in 1957, was reviewed. Straus, one of the founders of medical sociology, made major contributions to this field and created the first department of behavior sciences in a medical school. In the work reviewed, Straus establishes the differences between sociology in medicine and medical sociology. Comments are made on the current perspective of medical sociology and about the author.